Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis Hypogaea L.) Pada Tanah Marginal Pesisir Pantai dengan Pemberian Berbagai Jenis Bahan Pembenah Tanah dan Dosis Pupuk TSP” - Dilla Safdia; Syukri Syukri; Adnan Adnan (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Marginal coastal land has not been able to be utilized optimally by communities around the coast for agriculture. So far, coastal sand land has limited management and is considered to be poor. With the limited beach sand land, efforts need to be made to increase its productivity by providing soil improvement materials and by the right way to fertilize. The aim of this research is to determine the effect of applying soil amendments and doses of TSP fertilizer to marginal coastal land. The location of this research was carried out in Sidorejo Village, Langsa Lama District, Langsa City with an altitude of ± 10 m above sea level. This research was structured using a factorial Randomized Block Design (RAK), as the first factor, namely the type of soil amendment material P1 (husk charcoal), P2 (wood charcoal), P3 (zeolite) and P4 (clay), the second factor was the level of TSP fertilizer dose, namely D0 (0 kg)/ha), D1 (100 kg/ha), D2 (150 kg/ha), D3 (200 kg/ha) and D4 (250 kg/ha). Data were analyzed using anova (F experiment) from the 5% and 1% levels. If the treatment has a real effect, then continue with the BNJ test at the 5% level. The research results showed that the type of soil amendment material had a very significant effect on the parameters of number of branches and number of pods per plant. The best results were found in the soil amendment type P2 (husk charcoal). And the dose of TSP fertilizer has a very significant effect on the number of pods per plant. The best results were obtained on D4 (25 g/polybag).